Development Tendencies of Public Policy in Construction of Multi-Story Houses in the Construction Field - Ro’zmetov Navro’zbek Ikramjanovich (Genius Journals, 2023)
This article talks about such issues as priorities of state policy in construction, its goals and objectives, importance, mainly the issue of providing affordable housing to the population in construction, its relevance, history, work that must be done by the state in order for the population to live in favorable conditions, and the importance of prosecutorial supervision in this. In the construction of apartment buildings and the Prevention of the problem of homelessness of the population, the experiences of new industrial states were studied and the issues of applying positive aspects to our legislation and practice were considered.
Keywords: Central office of the state; planned economy; investments